Protecting Rice Grains in the Post-Genomic Era 2019
DOI: 10.5772/intechopen.84980
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Resistance of US Rice Breeding Lines to the Rice Blast Pathogen

Abstract: Rice blast, caused by the fungus Magnaporthe oryzae (anamorph: Pyricularia oryzae), is a ubiquitous disease that threatens rice production in the USA and worldwide. Growing resistant cultivars is the most economical and effective way to manage this disease. Multiple races exist in the M. oryzae population in the USA. It is necessary to know the resistance spectrum of rice cultivars to the prevalent rice blast races in the areas where they are grown. Twelve isolates of M. oryzae collected from the southern US r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…2). Mounting evidence has shown that Pi9(t) and Pita-2 are highly resistant to all rice blast isolates, 3,[27][28][29][30][31][32][33][34][36][37][38] indicating that Pi9(t) and Pita-2 are broadly resistant to P. oryzae. However, Pia, Pii, Pik-s, Piz-t, Pit, Pi3, and Pi5(t) are not resistant to the test isolates, which may be attributed to high genetic similarities of the ten rice cultivars (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Mounting evidence has shown that Pi9(t) and Pita-2 are highly resistant to all rice blast isolates, 3,[27][28][29][30][31][32][33][34][36][37][38] indicating that Pi9(t) and Pita-2 are broadly resistant to P. oryzae. However, Pia, Pii, Pik-s, Piz-t, Pit, Pi3, and Pi5(t) are not resistant to the test isolates, which may be attributed to high genetic similarities of the ten rice cultivars (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…26 Many studies have found that Pi9(t) and Pita-2 exhibit a broad spectrum resistance to P. oryzae using MLs DVs. 3,[27][28][29][30][31][32][33][34][35][36][37][38] The population of the rice blast fungus in the fields was intensively investigated during 1960-1990 in Taiwan. Chien classified 1871 isolates of Taiwan rice blast fungus collected between 1960 and 1987 into 78 physiological races and seven groups using Taiwan DVs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation